Three successful ways for k doping ZnO sol – gel synthesis - Abdulaziz Alkhattaby, Lila (Journal of King Abdulaziz University: Science, 2024)
One of the most frequently major challenges in the recent research is controlling the doping type I will prepare Zn1-x kx O once n-type and once p-type by dusting the type of reaction medium. Therefore, we transformed its preparation in three different ways or methods. In the first method, I use the strong base (KOH) that is much used in the electrical industry and managed to get n-type k doped ZnO, the second method uses halide metal salt (KCl) much used in the medical industry and managed to get p-type k doped ZnO and in the third method, I have used potassium acetate (CH3 CO2 K ) hilly cooler use in fire extinguishing and polymer industrial purposes. All methods managed to show Zn1-x Kx O nanopowder. The morphology analysis studies with the x-ray spectroscopy show ZnO patterns at (100), (002), (101), (102), (110), (103), (112), and (202), the EDX spectroscopy prove doped of potassium in the zinc oxide and show peaks of Zn, K, and O with no impurity while Zn and O are major elements And the scanning electron microscope SEM show hexagonal wurtzite structure for alkali media and dray method. In the acidic media, we managed to get the unstable cube structure ZnO It is a rare formula due to its instability, as the zinc oxide crystal quickly morphs into a hexagon. We have found that it is better to use potassium hydroxide with zinc chloride for electric devise manufacturing and potassium chloride with zinc chloride for photoelectric devise manufacturing.